A lineal air duct sprayer - PASTRO, John Emilio (2023)
The invention comprises a sprayer for spraying plants comprising an assembly of at least two lineal air ducts modules wherein each lineal air duct module comprises an axial fan mounted upon a single duct manifold wherein the air flow generated by the axial fan is directed into the single duct manifold which has a single lineal duct outlet which has mounted in the duct outlet plurality of vanes and spray nozzles for depositing liquid droplets into the air flow and directing the air flow containing the aerosolised particles towards the plants and wherein the duct manifold comprises a tapered duct in which the portion of the duct adjacent the axial fan has a wider cross section than the portion of the duct adjacent the bottom of the lineal duct outlet and wherein the vanes contained within the duct outlet are adjustable and the duct further comprises at least one air deflector for directing the airflow exiting the lineal air duct towards the subject plants. O::Ir1l'/O - . .30 Fig I